Analisis Pemasaran Ikan Lele di Gampong Lamdingin Kecamatan Kuta Alam Kota Banda Aceh - Nasrul Voorwanto; M. Nasir Ismail; Teuku Fadhla (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Catfish is a freshwater fish that has economic value. One of the African catfish cultivation centers is in Gampong Lamdingin, Kuta Alam District, Banda Aceh City. This research aims to find out what kinds of catfish marketing channel patterns exist, the duties and functions of the marketing institutions involved, and analyze the efficiency of catfish marketing. This research method is a descriptive and survey method with a location chosen deliberately, namely Gampong Lamdingin, Kuta Alam District, Banda Aceh City. Sampling was carried out using the Random Sampling method, marketing institution respondents were determined using the Snowball sampling method. Data collection techniques use interview techniques. Data analysis uses marketing margin analysis and farmer's share. The results of the research are: there are 2 marketing channel patterns for African catfish in Gampong Lamdingin, Kuta Alam District, Banda Aceh City, showing marketing channel 1 (farmer - retailer - consumer), marketing channel 2 (farmer - collector - retailer - consumer), efficiency The highest marketing of fish in Gampong Lamdingin, Kuta Alam District, Banda City is in the 1 level marketing channel with a margin value of IDR 7,119 per kg and the highest Farmer's share, namely 71.42%. The margin value for marketing channel 2 is IDR 8,476 per kg with a Farmer's share value of 64.28%. Marketing of catfish in Gampong Lamdingin, Kuta Alam District, Banda Aceh City is efficient, because the marketing efficiency value of marketing channel 1 level, marketing channel 2 farmer's share value is more than 60%